Penguatan Partai Politik sebagai Salah Satu Bentuk Pengadministrasian dan Pelembagaan Sistem Demokrasi - Aprista Ristyawati (Administrative Law and Governance Journal, 2019)
This study aims to determine the strengthening of political parties as a form of administration and institutionalization of democracy. The formulation of the problem in this study is: what are the main issues of political parties in Indonesia at this time and how are efforts to strengthen political parties as a form of democratic institutionalization. The method of approach used in this study is normative juridical and analytical descriptive that is describing the object that is the main problem, from the depiction taken an analysis that is adapted to existing legal theories and put the law as a norm system building. The results of this study indicate that there are 3 (three) Main Problems of Political Parties in Indonesia that occur at this time, namely the weakening ideology of political parties, the recruitment system and the cadre formation patterns of less qualified political party members, the crisis of fundraising / fundraising of political parties. Efforts must be made to strengthen political parties as a form of institutionalization of democracy, namely using the ideology of political parties that must be strengthened, improve the quality and strengthen the recruitment system and regeneration patterns of political party members and there must also be a strengthening of the political party's fundraising system.Keywords: Political Parties, institutionalization of democracy Abstrak Penelitian ini bertujuan tuntuk mengetahui penguatan partai politik sebagai salah satu bentuk pelembagaan demokrasi. Metode pendekatan yang digunakan dalam penelitian ini adalah yuridis normatif dan bersifat deskriptif analitis yaitu menggambarkan objek yang menjadi pokok permasalahan, dari penggambaran tersebut diambil suatu analisa yang disesuaikan dengan teori-teori hukum yang ada dan meletakan hukum sebagai sebuah bangunan sistem norma. Hasil penelitian ini menunjukkan bahwa Ada 3 (tiga) Problem Utama Partai Politik di Indonesia yang terjadi pada saat ini, yaitu ideologi partai politik yang semakin melemah, sistem rekrutmen dan pola kaderisasi anggota partai politik yang kurang berkualitas, krisis pengumpulan dana / Fundraising pada partai politik. Upaya yang harus dilakukan untuk memperkuat Partai Politik sebagai salah satu bentuk pelembagaan Demokrasi yaitu dengan cara ideologi Partai Politik harus diperkuat, meningkatkan kualitas dan memperkuat sistem rekrutmen dan pola kaderisasi anggota partai politik dan juga harus ada penguatan sistem pengumpulan dana (Fundraising) Partai Politik. Kata Kunci : Partai Politik, pelembagaan demokrasi